THE TRANSMISSION OF MODERN SALAFI REFORMIST IDEAS TO THE MALAY PENINSULA (LATE 19TH – EARLY 20TH CENTURIES): MECHANISMS AND FACTORS OF INFLUENCE (Eureka Journal of Humanities and Social Research, 2026)
This article examines the multifaceted process of transmitting Islamic reformist ideas (*islah*) to the Malay Peninsula during the period of systemic transformations at the turn of the 20th century. The author analyzes the roles of the Haramayn, Cairo, and print technology as key channels through which the ideas of Muhammad Abduh and Rashid Rida penetrated the Malay world. Particular attention is paid to the shift from traditional forms of education to politicized student activism and the role of intellectual intermediaries in localizing reformist discourse. The study’s novelty lies in its synthesis of material-technical factors (the opening of the Suez Canal, the development of steamship travel) and the intellectual networks that shaped a new Malay self-awareness amidst colonial pressure.
Keywords: Salafiyya, Islamic reformism, Malay Peninsula, Al-Azhar, *Al-Manar*, Haramayn, transmission of ideas, Jawi, *ijtihad*, Muhammad Abduh.